Meta Analysis: Effect of Exclusive Breastfeeding on Child’s Development - Dwiantini, Feby; Pamungkasari, Eti Poncorini; Adriani, Rita Benya (Journal of Maternal and Child Health, 2024)
Background: Breast milk contains enough nutritional content for infants aged 0 to 6 months even without additional food. Exclusive breastfeeding has a positive impact on growth and development disorders experienced by babies. This study aimed to analyze and estimate the effect size of exclusive breastfeeding on 5 areas of child development, namely gross motor, fine motor, communication, problem solving and personal social. Subjects and Method: It was a meta-analysis study conducted in accordance to PRISMA flow chart and PICO. Population= children aged 6 months to 5 years. Intervention= exclusive breastfeeding. Comparison= non-exclusive breastfeeding. Outcome= child development (gross motor, fine motor, communication, problem solving, and personal social). Articles were obtained from Google Schoolar, Science Direct, and PubMed. Inclusion criterias were cohort study, full text article, and child development measurement using the ages & stages questionnaire. Data analysis was conducted using Revman 5.3. Results: 8 cohort studies from the America, Australia, Europe, Africa, and Asia were selected for meta-analysis. Total sample was 22,048. Exclusive breastfeeding increased child’s development (aOR= 1.07; 95% CI= 1.04 to 1.10; p < 0.001). Exclusive breastfeeding had a positive effect on all five areas of gross motor development (aOR= 1.05; 95% CI= 1.00 to 1.10; p= 0.030), fine motor (aOR= 1.10; 95% CI= 1.02 to 1.18; p= 0.009), communication (aOR= 1.06; 95% CI = 1.01 to 1.11; p= 0.020), problem solving (aOR= 1.12; 95% CI= 1.02 to 1.21; p= 0.010) and personal social (aOR= 1.10; 95% CI= 1.03 to 1.17; p= 0.005). Conclusion: Exclusive breastfeeding significantly increases child’s development.